Combustion Characteristics for Turbulent Prevaporized Premixed Flame Using Commercial Light Diesel and Kerosene Fuels - Mohamed S. Shehata; Mohamed M. ElKotb; Hindawi Salem (Journal of Combustion)
Experimental study has been carried out for investigating fuel type, fuel blends, equivalence ratio, Reynolds number, inlet mixture temperature, and holes diameter of perforated plate affecting combustion process for turbulent prevaporized premixed air flames for different operating conditions. CO2, CO, H2, N2, C3H8, C2H6, C2H4, flame temperature, and gas flow velocity are measured along flame axis for different operating conditions. Gas chromatographic (GC) and CO/CO2 infrared gas analyzer are used for measuring different species. Temperature is measured using thermocouple technique. Gas flow velocity is measured using pitot tube technique. The effect of kerosene percentage on concentration, flame temperature, and gas flow velocity is not linearly dependent. Correlations for adiabatic flame temperature for diesel and kerosene-air flames are obtained as function of mixture strength, fuel type, and inlet mixture temperature. Effect of equivalence ratio on combustion process for light diesel-air flame is greater than for kerosene-air flame. Flame temperature increases with increased Reynolds number for different operating conditions. Effect of Reynolds number on combustion process for light diesel flame is greater than for kerosene flame and also for rich flame is greater than for lean flame. The present work contributes to design and development of lean prevaporized premixed (LPP) gas turbine combustors.